Crowd noise as a cue in referee decisions contributes to the home advantage - Unkelbach, C.; Memmert, D. (Journal of Sport & Exercise Psychology, 2010)
The home advantage is one of the best established phenomena in sports (Courneya & Carron, 1992), and crowd noise has been suggested as one of its determinants (Nevill & Holder, 1999). However, the psychological processes that mediate crowd noise influence and its contribution to the home advantage are still unclear. We propose that crowd noise correlates with the criteria referees have to judge. As crowd noise is a valid cue, referee decisions are strongly influenced by crowd noise. Yet, when audiences are not impartial, a home advantage arises. Using soccer as an example, we show the relevance of this influence in predicting outcomes of real games via a database analysis. Then we experimentally demonstrate the influence of crowd noise on referees` yellow cards decisions in soccer. Finally, we discuss why the focus on referee decisions is useful, and how more experimental research could benefit investigations of the home advantage.